Resistance to acute Trypanosoma cruzi infection resulting from immunization of mice with a 90-kilodalton antigen from metacyclic trypomastigotes. - González, J (1991)
The stage-specific 90-kDa surface antigen of Trypanosoma cruzi metacyclic trypomastigotes was affinity purified and used for immunization studies. Mice immunized with the 90-kDa antigen plus alum as an adjuvant were resistant to challenge with Tulahuen strain metacyclic forms, displaying either reduced or subpatent parasitemias. Mice immunized with the purified antigen without adjuvant or with antigen plus Freund adjuvant or glucan developed high parasitemias, comparable to those of nonimmunized controls, upon metacyclic challenge. Sera of mice immunized with the 90-kDa antigen plus alum showed complement-dependent trypanolytic activity and also greatly inhibited the invasion of Vero cells by metacyclic forms of G and Tulahuen strains in vitro. These sera were found by a competition binding assay to contain antibodies that recognized the same or topographically related sites as the monoclonal antibody 1G7, an antibody previously shown to reduce the infectivity of metacyclic forms in vivo and in vitro. In contrast, 1G7-related antibodies were poorly represented in sera with negative or low trypanolytic activity, such as those from mice immunized with purified antigen without adjuvant.